Global actions for Sustainable Rangelands and Pastoralism to achieve Land Degradation Neutrality - Masumbuko, Bora; Louhaichi, Mounir; Niamir-Fuller, Maryam (International Center for Agricultural Research in the Dry Areas, 2023)
This presentation focuses on the global actions required to achieve Land Degradation Neutrality (LDN) through sustainable rangelands and pastoralism, aligning with the International Year for Rangelands and Pastoralists (IYRP) and its sub-working group on LDN. The challenges and threats to rangelands are outlined, emphasizing the climatic and anthropogenic pressures leading to natural resource degradation, productivity losses, and land-related conflicts. Notably, the presentation highlights the global average rate of rangeland degradation, conversion to croplands, and the various drivers contributing to this phenomenon.